Accounting Information System of Distributor Company: Controls That Should Be Taken Into Account (Case Study of Pt. S) - Vania Nita; Machmudin Eka Prasetya (E-Jurnal Akuntansi, 2025)
The effectiveness of internal control in the accounting information system of a mid-sized distribution company remains an underexplored topic in research. Using the template analysis method, a case study was conducted at a mid-sized distribution company. Various issues and fraudulent activities were identified within the company. This study aims to uncover the root causes by analyzing the internal control of the company’s revenue and expenditure cycles using the COSO Framework. The study also examines the impact of internal control weaknesses in the context of the Fraud Hexagon. The research finds that there is a general lack of implementation of internal control within the accounting information system, which triggers various fraud motivations. The company needs to optimize the use of the Distribution Management System in its daily operations, especially in bookkeeping. This study contributes to the literature by emphasizing the importance of implementing internal control in accounting information systems in distribution companies.